Applied OHS With Empirical Ergonomics and Hazard Methods to Minimize Fatigue at KPPS Cerme Gresik - Nurcahyanie, Yunia Dwie; Yulianto, Muhammad Teguh (Tibuana, 2024)
To support fair, honest, and Luber Jurdil elections, public awareness about the importance of healthy politics needs to be increased. Voters who have registered for the permanent election (DPT) must cast five ballots in the 2019 simultaneous elections. Voter participation in the 2019 elections, which reached 81.97%, and legislative participation (Pileg) in 2019, which reached 81.69%, showed a fairly good election organization in 2019. However, this is at odds with the health and safety of KPPS officers. According to the KPU RI, the number of election organizers who died in the 2019 elections was 11,239, with 527 victims dying, based on the results of the Ministry of Health's investigation in 28 provinces. Based on the investigation and analysis of the Indonesian Ministry of Health, the fatigue factor triggered the disease suffered by polling station officers. It is necessary to conduct ergonomic research on KPPS officers in the 2024 elections, which is useful for developing an election polling station model that is comfortable, safe, healthy, effective, and efficient so as to reduce factors that cause fatigue while working. The components studied include workload components, rest time, or the physical work environment at election polling stations. The data collection methods used in this research are observation, interview, direct data, and literature study.The analysis used in this study produces a list of events and classifies the incidence of fatigue of KPPS officers, the most problematic workplace. fatigue classification, Identifying Ergonomic Risk Factor (ERF), Data processing, Analysis and discussion as well as conclusions and suggestions.